2018
DOI: 10.1002/ieam.4035
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of the application of polymer of low concern and regulatory criteria to fluoropolymers

Abstract: Per- and polyfluoroalkyl substances (PFAS) are a group of fluorinated substances that are in the focus of researchers and regulators due to widespread presence in the environment and biota, including humans, of perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA). Fluoropolymers, high molecular weight polymers, have unique properties that constitute a distinct class within the PFAS group. Fluoropolymers have thermal, chemical, photochemical, hydrolytic, oxidative, and biological stability. They h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
151
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 37 publications
2
151
0
2
Order By: Relevance
“…3,54,62 The safety evaluation of these devices for use in humans was discussed by Henry et al (2018). 63 Aer review, multiple regulatory agencies have concluded that the use of PFASs in these products, including in devices implanted into patients' bodies, does not pose an appreciable risk because the uoropolymers are not bioavailable. [63][64][65] It is however unclear whether impurities of uoropolymer processing aids such as PFOA and HFPO-DA were included in the regulatory reviews.…”
Section: Case Studies Of Uses Of Pfassmentioning
confidence: 99%
“…3,54,62 The safety evaluation of these devices for use in humans was discussed by Henry et al (2018). 63 Aer review, multiple regulatory agencies have concluded that the use of PFASs in these products, including in devices implanted into patients' bodies, does not pose an appreciable risk because the uoropolymers are not bioavailable. [63][64][65] It is however unclear whether impurities of uoropolymer processing aids such as PFOA and HFPO-DA were included in the regulatory reviews.…”
Section: Case Studies Of Uses Of Pfassmentioning
confidence: 99%
“…Another use of fluoropolymers is as coatings in catheters, stents and needles to reduce friction and improve clot resistance and to provide protein-resistance in filters, tubing, o-rings, seals, and gaskets used in kidney dialysis machines and immunodiagnostic instruments 3,54,62 . The safety evaluation of these devices for use in humans was discussed by Henry et al (2018). 63 After review, multiple regulatory agencies have concluded that the use of PFASs in these products, including on devices implanted into patients' bodies, does not pose an appreciable risk because the fluoropolymers are not bioavailable [63][64][65] .…”
Section: Medical Devicesmentioning
confidence: 99%
“…The safety evaluation of these devices for use in humans was discussed by Henry et al (2018). 63 After review, multiple regulatory agencies have concluded that the use of PFASs in these products, including on devices implanted into patients' bodies, does not pose an appreciable risk because the fluoropolymers are not bioavailable [63][64][65] . It is however unclear whether impurities of fluoropolymer processing aids such as PFOA and HFPO-DA were included in the regulatory reviews.…”
Section: Medical Devicesmentioning
confidence: 99%
“…Hence fluorine-based polymers are recognized as great value-added molecules owing to their versatile unique feature particularly low value of refractive index, cohesive energy, surface energy and relative permittivity, and high value of thermal resistance, high chemical stability, resistance against UV, concentrated mineral acids, alkalis, and aging [76][77][78]. The tradename of commercially available Fluoropolymers has been tabulated in Table 5.…”
Section: Selection Of the Coating Materialsmentioning
confidence: 99%
“…Although these coatings served the purpose of improved anti-galling properties but the fluorine present in them act as a biotransformation precursor i.e. it results in the metabolism imbalance in human body and sometime can result in trauma as during austere conditions fluoro-polymers gets degrade and releases hydrofluoric acids [77,172].…”
Section: Limitation Of Fluoro-based Polymersmentioning
confidence: 99%